Strategi pengadaan bahan baku agroindustri daun kelor berkelanjutan (studi kasus CV. Tri Utami Jaya di Mataram Provinsi Nusa Tenggara Barat) - M. Agusfian; Machfud Machfud; Faqih Udin (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
CV. Tri Utami Jaya is an agricultural processing industry that utilizes moringa leaves in various product variants. The problem faced by CV. Tri Utami Jaya has a large capacity but idle capacity. Namely the production capacity that can be used by large companies are companies can use it. In reality, the capacity is not used (idle). In addition, I learned about the challenges faced by CV. Tri Utami Jaya with market potential, is in high demand while the need for raw materials is still fluctuating. The purpose of this study is to determine the need for accurate raw material procurement using the Auto Regressive Integrated Moving Average (ARIMA) model in order to obtain the most optimal prediction results, analyze internal and external factors that influence raw material procurement, and obtain a sustainable moringa leaf agroindustry raw material procurement strategy in terms of fulfillment and minimal risk. This research stage begins with a field study that will include interviews with moringa leaf agroindustry actors. The analysis method used is a combination of SWOT (Strengths, Weaknesses, Opportunities, Threats) and Analytical Hierarchy Process (AHP) techniques to obtain strategic priorities. The results of this study found two clusters, namely raw material fulfillment strategies and procurement risk reduction strategies. Furthermore, the first priority strategy alternative is to utilize the availability of large land in NTB (core plantations and partnerships), capital assistance for farmers, and government support in planting moringa by involving local workers, with a score of 0.3156. The second priority strategy is socialization to encourage farmers to replant moringa by ensuring higher profits from moringa leaf commodities with a score of 0.1979. The third priority strategy is to maximize the use of storage warehouses to accommodate and store raw materials in large quantities when availability is high, in order to face the threat of reduced availability of raw materials and weather uncertainty with a score of 0.1768.